2011
DOI: 10.1590/s1806-37132011000600002
|View full text |Cite
|
Sign up to set email alerts
|

Controle da asma e qualidade de vida em pacientes com asma moderada ou grave

Abstract: Objective: To evaluate the association between degree of asthma control and health-related quality of life in patients with moderate or severe asthma. Methods: This was a descriptive observational study involving 59 outpatients with moderate or severe asthma under treatment at the Asthma Outpatient Clinic of the Federal University of Ceará Walter Cantídio University Hospital, in the city of Fortaleza, Brazil. The patients were evaluated regarding sociodemographic and clinical characteristics, as well as spirom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 17 publications
1
12
0
5
Order By: Relevance
“…This result is consistent with those of a study showing that patients with controlled asthma have a better quality of life than do those with uncontrolled asthma. ( 22 ) However, although the mean score for the activity limitation domain and that for the symptoms domain were equal, the activity limitation domain showed the lowest scores; this constitutes evidence that the asthma patients had lower exercise tolerance, which affected their quality of life. ( 4 - 6 ) …”
Section: Discussionmentioning
confidence: 97%
“…This result is consistent with those of a study showing that patients with controlled asthma have a better quality of life than do those with uncontrolled asthma. ( 22 ) However, although the mean score for the activity limitation domain and that for the symptoms domain were equal, the activity limitation domain showed the lowest scores; this constitutes evidence that the asthma patients had lower exercise tolerance, which affected their quality of life. ( 4 - 6 ) …”
Section: Discussionmentioning
confidence: 97%
“…Pereira et al in a study on QoL in asthma[18] showed that the ACT scores were statistically correlated with the QoL ( r = −0.72; P < 0.01), symptoms improvement ( r = −0.78; P < 0.01) and better physical activity ( r = −0.67; P < 0.01); which may means that better asthma control scores may translates to better QoL. Another study by Ko et al [19] demonstrated that the measurement of ACT is useful for assessing asthma control, prediction of exacerbation, and changes in treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The Standardized AQLQ[1819] was selected for the work and it consists of 32 questions with a 7-point scale of responses for each (e.g., 1 = totally limited to 7 = not at all limited). The questions were grouped into four domains which was based on the symptoms (all generic), activity limitations, emotional function, and environmental stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…The severity and presence of asthma symptoms are known factors that affectQoLfor individuals with asthma and their families [5,6]. Asthma attacks can cause considerable QoL burden and strain that may last a lifetime [7].…”
Section: Introductionmentioning
confidence: 99%